Mortality among goats due to parasitic infections : A postmortem analysis - SHARMA, D K; SINGH, NEM (The Indian Journal of Animal Sciences, 2013)
Mortality figures due to parasitic infections among goats at 3 goat farms of Jamunapari, Barbari and Jakhrana breeds, maintained under semi-intensive system of management and located in the semi-arid tropical region, have been analysed in breed susceptibility, seasonal variations and age-wise distribution. Out of 2 538 postmortems (conducted between 1986 and 1994),325 (12.8%) goats died due to different parasitic diseases. Parasitic deaths amongst these goats were due to coccidiosis (6.70%), haemonchosis (3.46%), hydatidosis (1.33%), coenurosis(1.14%) and monieziasis (0.15). Mortality due to coccidiosis was more common from March to May and Jul)( to September, whereas deaths due to haemonchosis were more during and after rainy season, Age-wise, deaths due to coccidiosis were restricted up to one year of age while in haemoochosis animals died more after pne year of age. Mortality due to hydatidosis and coenurosis was distributed in all age groups except in kids( 0-3 M) without showing seasonal inclination.